Hubungan Riwayat Kelahiran Prematur dan BBLR dengan Gangguan Pendengaran pada Anak di RSUP Haji Adam Malik Periode 2016-2018 - Sonyalita Gultom; Andrina Y. M. Rambe (Scripta Score Scientific Medical Journal, 2021)
Background: Children with preterm labor and low birth weight history tend to suffer various health complications, from growth and development problems, inadequate organ functions, and central nervous system disturbances. Hearing impairment is the most common health problem that occurs in children with preterm labor and low birth weight history. Hearing impairment affects speech and language learning in children, since children need to comprehend various types of voices to learn speech and language thoroughly. Hearing examination is important to be done as early as possible. Hearing function can be examined as newborns reached 2 days after labor (48 hours). Hearing examination that is recommended for babies and children is Otoacoustic Emission (OAE) examination, since it is easy to conduct, no requirement for trained operator, is safe, and objectively accurate.